Assessment of Welfare Packages in Secondary Schools: An Implication on Educational Managers - Ayoku, Oba Baba; Owoyale-Abdulganiy, Ibrahim Solahudeen; AbdulRasaki, Salihu (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
This research examines the welfare packages implemented in secondary schools and their implications for educational managers. Key welfare components include financial benefits, health services, professional development opportunities, and work-life balance initiatives. These packages enhance the well-being of teachers and students, improve retention rates, motivation, and productivity, and emphasize the role of educational managers in effective implementation and management. The study also addresses challenges faced by managers in integrating comprehensive welfare strategies, such as budget constraints, policy limitations, and varying stakeholder expectations. The findings suggest that a well-structured welfare package can lead to a more engaged and effective teaching workforce, ultimately improving student outcomes. This research provides valuable insights for educational managers seeking to foster a supportive learning environment and advocates for a holistic approach to educational management that prioritizes the welfare of both educators and students. The study serves as a foundational reference for educational stakeholders interested in understanding the interplay between welfare packages and educational management, urging a shift towards a more welfare-oriented approach in secondary education settings.